2014
DOI: 10.1093/fampra/cmu051
|View full text |Cite
|
Sign up to set email alerts
|

Acute low back pain management in general practice: uncertainty and conflicting certainties

Abstract: GPs' initial focus upon tissue injury during acute care, and providing a diagnostic label, may influence patients' subsequent alignment with a biomedical perspective and contribute to consultation conflict and patients' perception of blame when discussion of psychosocial influences is introduced. Demonstrating the relevance of the biopsychosocial model to acute LBP may improve GPs' alignment with guidelines, improve their confidence to manage these patients and ultimately improve outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
55
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(55 citation statements)
references
References 46 publications
0
55
0
Order By: Relevance
“…The latter consideration may be particularly important to clinicians who perceive themselves as vulnerable to litigation and are challenged by the need to exclude the possibility of serious pathology within short consultation times. [13][14][15] Even in situations where the GP advises against imaging, patient expectations (along with GP perceptions of the expectations of their patients) may nonetheless lead to referral. In Australia, spinal imaging is widely available and easily organised via an abundance of private radiology companies.…”
Section: Low Back Painmentioning
confidence: 99%
“…The latter consideration may be particularly important to clinicians who perceive themselves as vulnerable to litigation and are challenged by the need to exclude the possibility of serious pathology within short consultation times. [13][14][15] Even in situations where the GP advises against imaging, patient expectations (along with GP perceptions of the expectations of their patients) may nonetheless lead to referral. In Australia, spinal imaging is widely available and easily organised via an abundance of private radiology companies.…”
Section: Low Back Painmentioning
confidence: 99%
“…It further stresses that also in patients with acute neck pain, the multidimensional approach of pain management should be present from the onset of treatment in order to improve outcome, which might not always be the case in daily clinical practice. In the management of acute low back pain, general practitioners were reported to understand pain as a direct representation of tissue injury, and therefore, assessment or management of attitudes and beliefs was of low priority [ 25 ]. However, it is well known that appropriate information and the patient’s understanding of pain is crucial in the treatment of acute LBP [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…We noted an underlying assumption by patients that severe LBP mandated spinal imaging and an accompanying biomechanical explanation. Previous studies have found that such beliefs and expectations primarily arise from earlier experiences of LBP care, the influence of family and friends, and comments from previously consulted health professionals . However, most clinical guidelines recommend patients with acute LBP do not require imaging unless there are ‘red flags’ present suggesting underlying pathology .…”
Section: Discussionmentioning
confidence: 99%